PENGARUH PENDELEGASIAN WEWENANG DAN KOMITMEN ORGANISASI TERHADAP KINERJA MANAJERIAL PADA ORGANISASI PERANGKAT DAERAH PEMERINTAH KOTA TANGERANG - Rabitha Fazira (Prosiding Simposium Nasional Multidisiplin (SinaMu), 2019)
The purpose of this research was to examine the influence of delegation of authority and organizational commitment to managerial performance in the regional government organizations in Tangerang City. This study distributed 61 questionnaires. Data analysis methods used by this research Partial Least Square (PLS). Stages of analysis with the method of designing a measurement model, test the outer model (validity and reliability), test the inner model (path coefficients), test the fit model (goodness of fit), hypothesis testing (resampling bootstraping) and conclusions.The results of the study found that delegation of authority had a significant positive effect on managerial performance and organizational commitment had a significant positive effect on managerialPerformance.Keywords: delegation of authority,organizational commitment, managerial performance